CUSTOMER INSIGHTS FOR DIGITAL TRANSFORMATION - Hoffmann, Alfredo A. (2020)
Many companies today say they are customer-centric and implementing digital transformation. We will address the first topic in this essay, which is thought to be the foundation and most importantly before beginning a process of digital transformation. Professor Peter Fader, from The Wharton School of the University of Pennsylvania, a university of preponderance, defines a customer centric company as one that knows its customers with greater future profitability and that aligns the development of products and the company's operations towards them.